Alternative calculation of the physical mass of the p-meson - Morones Ramírez, Rubén; Mejía Rosales, Sergio (World Scientific Publishing Company, 2005)
We have derived an expression for the physical mass and width of the ρ-meson in vacuum from its spectral function, calculated in the vector meson dominance model when a ρ 0 meson couples to two virtual pions π +–π −. The propagator is computed after evaluating the ρ-meson self-energy. The real part of the ρ-meson self-energy is given by a divergent integral and needs to be regularized; the regularization is done by using a double subtracted dispersion relation. The result leads to a closed analytical expression which allow us to evaluate the spectral function in a closed way. The physical mass, defined as the magnitude of the four-momentum |k| for which the spectral function S(k 2 ) attains its maximum value, is obtained, and it gives a value of 770 MeV, which is in total agreement with the reported experimental value of the ρ-meson mass